2018
DOI: 10.1002/lary.27170
|View full text |Cite
|
Sign up to set email alerts
|

A new method for selecting auricle positions in skull base reconstruction for temporal bone cancer

Abstract: 4 Laryngoscope, 2605-2610, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Musculocutaneous submental flap is an excellent option with reduced operative time, hospitalization duration, and flap revisions, because of its proximity, reliability, ease of harvest, and exceptional color match [ 31 ]. Tanaka et al reported a new method for selecting intraoperative accurate auricle positions in skull base reconstruction for advanced temporal bone carcinoma cases, so that auricle can be preserved as much as possible from a cosmetic and functional perspective [ 32 ]. Morita et al have shown that reconstruction of the EAC using split-thickness skin graft in combination with tympanoplasty can preserve hearing after LTBR for early-stage external auditory canal carcinoma [ 33 ].…”
Section: Treatmentmentioning
confidence: 99%
“…Musculocutaneous submental flap is an excellent option with reduced operative time, hospitalization duration, and flap revisions, because of its proximity, reliability, ease of harvest, and exceptional color match [ 31 ]. Tanaka et al reported a new method for selecting intraoperative accurate auricle positions in skull base reconstruction for advanced temporal bone carcinoma cases, so that auricle can be preserved as much as possible from a cosmetic and functional perspective [ 32 ]. Morita et al have shown that reconstruction of the EAC using split-thickness skin graft in combination with tympanoplasty can preserve hearing after LTBR for early-stage external auditory canal carcinoma [ 33 ].…”
Section: Treatmentmentioning
confidence: 99%
“…Since natural auricles have evident advantages in wearing glasses or masks, resistance to trauma, and esthetic appearance, auricle-conserving surgery should be encouraged for exploration, especially in the case of the EAC and/or middle ear carcinoma. Tanaka et al 5 reported a study regarding lateral skull reconstruction by the ALT flap while preserving most of the auricle. The operation began with a long transcranial incision, subgaleal dissection, and a large flap with the remaining auricle.…”
Section: An Active Role Of Reconstructive Surgeon In Otologic Tumor Surgerymentioning
confidence: 99%